Challenges in simulating robotics and automation systems for real world applications utilising project based courses - Abdul Hamid, Syamsul Bahrin; Md Yusuf, Hazlina; Abd Latif, Muhamad Hafiz (IEEE, 2015)
In any engineering project, there is a need for a good framework and implementation process which are able to propagate effectively from the conceptual and detail design, to conducting simulation of the finalized design and finally creating a physical presence through assembly and prototyping process. Although these requirements could be generalized for any engineering project, it is much more imperative that in robotic design this is conducted as such, due to the various sensors, actuators and control requirements needed to integrate a system. This process is important since a fully integrated robotic system need to be fully optimized for it to be able to perform the required and desired function effectively.